Melukat as Hydro-Spiritual Healing in Balinese Wellness Tourism: An Ethnomedical Study of Ritual, Natural, and Psychosomatic Well-Being - I Gusti Intan Ayu Pramesti Utami; Made Budiawan; Made Ajiswara Laba; Veronica Aurelie Buntoro; Ayu Putu Githa Maheswari; Laras Nazillah Putri (PROMOTOR, 2026)
Melukat is a Balinese cultural tradition aimed at cleansing the soul and mind of negative energy. Today, melukat has become widespread and sought after as a form of spiritual practice popular in wellness tourism. This study aims to determine how melukat as a hydro-spiritual practice is viewed from an ethnomedical perspective. This study is a qualitative study with a phenomenological approach. Data were collected through interviews with priests and melukat practitioners. The results indicate that melukat is also a hydro-spiritual therapy process that integrates ritual, nature, and the balance of body and soul. Interviews with respondents revealed that melukat is considered a self-purification effort to achieve cleanliness and peace of mind. From an ethnomedical perspective, the practice of melukat represents a traditional healing system that remains relevant as global spiritual tourism grows. Melukat demonstrates that local cultural traditions can be a valuable source of comprehensive healing for Balinese people and tourists seeking spiritual experiences.